2021
DOI: 10.3389/frvir.2021.722321
|View full text |Cite
|
Sign up to set email alerts
|

Ambisonics Sound Source Localization With Varying Amount of Visual Information in Virtual Reality

Abstract: To reproduce realistic audio-visual scenarios in the laboratory, Ambisonics is often used to reproduce a sound field over loudspeakers and virtual reality (VR) glasses are used to present visual information. Both technologies have been shown to be suitable for research. However, the combination of both technologies, Ambisonics and VR glasses, might affect the spatial cues for auditory localization and thus, the localization percept. Here, we investigated how VR glasses affect the localization of virtual sound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…While artificial reverberation has historically been used as a tool for artistic expression (Välimäki et al, 2012), room acoustics simulations are also utilized for planning of spaces (e.g., concert halls and classrooms; Rindel, 2001). Recently, room acoustics simulations and virtual acoustic environments (VAEs) have gained interest as tools for psychoacoustic research and hearing aid development (Ahrens et al, 2019; Grimm et al, 2019; Huisman et al, 2019; Pausch & Fels, 2020; Pausch & Fels, 2020; Rindel, 2001; Schutte et al, 2019; Seeber et al, 2010), particularly in the context of ecological validity, where the results of speech-in-noise and hearing test with simplified “synthetic” stimuli have been questioned with regard to real-world outcomes (Cord et al, 2007; Jerger, 2009; Keidser et al, 2020; Miles et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While artificial reverberation has historically been used as a tool for artistic expression (Välimäki et al, 2012), room acoustics simulations are also utilized for planning of spaces (e.g., concert halls and classrooms; Rindel, 2001). Recently, room acoustics simulations and virtual acoustic environments (VAEs) have gained interest as tools for psychoacoustic research and hearing aid development (Ahrens et al, 2019; Grimm et al, 2019; Huisman et al, 2019; Pausch & Fels, 2020; Pausch & Fels, 2020; Rindel, 2001; Schutte et al, 2019; Seeber et al, 2010), particularly in the context of ecological validity, where the results of speech-in-noise and hearing test with simplified “synthetic” stimuli have been questioned with regard to real-world outcomes (Cord et al, 2007; Jerger, 2009; Keidser et al, 2020; Miles et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Wearing a VR headset likely affected the listener's HRTFs 32 , potentially resulting in localization errors and different movement behavior compared to real-world scenarios. However, studies by Ahrens et al 15 and Huisman et al 45 suggest that the influence of VR headset on sound localization accuracy is minimal when ample visual information is provided. Nonetheless, the impact of VR headsets on movement behavior remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…The participants tended to overestimate the lateral position of the lateral targets with the three visual-to-auditory encodings: a shift to the left for targets on the left, and a shift to the right for targets on the right. Some studies also showed an overestimation pattern of lateral sound sources while using non-individualized HRTFs (Wenzel et al, 1993 ), in a virtual environment while being blindfolded (Ahrens et al, 2019 ), using ambisonics (Huisman et al, 2021 ), and even with real sound sources (Oldfield and Parker, 1984 ; Makous and Middlebrooks, 1990 ). A possibility to decrease this overestimation might be to rescale the used HRTF positions to fit to the perceived ones.…”
Section: Discussionmentioning
confidence: 99%